Cultivation of Character Education Through Learning to Listen to Speech Based on Flash Media in the Digital Age - Riswanda Himawan; Ariesty Fujiastuti; Iis Suwartini (Universitas Sebelas Maret, 2020)
In the era of 4.0 technological advances that developed very rapidly indirectly affected all aspects of human life, both in the political, economic, cultural, even in the field of education. Every technology must have both positive and negative impacts. Positive benefits that can be obtained from technological advancements are providing facilities in the field of Education. One way that can be done is to use Flash as a learning media to listen to speeches for students which of course there are character values that can be developed in the media. The character developed in this media is the character of independence because students are highly required to work independently in the learning process. In addition, the characters developed in this media are the characters who love the environment, it can be seen from the contents of the speech that invites the listener to love the environment together. The purpose of this paper, which is to find out how to inculcate character education through learning to listen to flashbased speeches in the digital age. This type of research is Reasrch and Develompent (R&D). Development is carried out by developing learning media listening to speeches using the Flash application. Data collection method using a questionnaire. The feasibility instrument is reviewed from the learning media. The data analysis technique used is descriptive analysis technique. The final stage of this development is the feasibility and effectiveness test. Based on the results of the study it can be seen that instilling character education can be done through listening to speeches using flash-based media. This learning media is designed to deal with the era of digitalization, in addition to this, there are also character values that can be developed, including the character of independence and also the character for love for nature. The value of the independence character in this media can be seen from the form of media where users can access and download the desired material themselves, the value of the character of nature's love in this case can be seen from the contents of the speech which will directly preserve listening to both protecting the environment